Discrimination by design : - Weisman, Leslie Kanes (University of Illinois Press, 1992)
This thoroughly readable book provides practical guidance to policymakers, architects, planners, and housing activists. It should be read by all who are interested in understanding how the built environment shapes the experiences of their daily lives